An Analysis of Serological Response and Infection Outcomes Following Oxford-AstraZeneca (AZD1222) and Pfizer-BioNTech (mRNA BNT162b2) SARS-CoV-2 Vaccines in Kidney and Kidney-pancreas Transplants. Issue 7 (8th March 2022) - Asderakis, Argiris; Khalid, Usman; Koimtzis, Georgios; Ponsford, Mark J.; Szabo, Laszlo; Chalklin, Christopher; Bramhall, Kathryn; Grant, Leanne; Moat, Stuart J.; Humphreys, Ian R.; Jolles, Stephen R.
Abstract : Background: Severe acute respiratory syndrome coronavirus 2 is associated with high mortality among transplant recipients. Comparative data that define humoral responses to the Oxford-AstraZeneca (AZ) and BNT162b2 (Pfizer-BioNTech) vaccines are limited. Methods: We recruited 920 kidney transplant patients receiving at least 1 dose of severe acute respiratory syndrome coronavirus 2 vaccine, excluding patients with virus pre-exposure. Serological status was determined with the COVID-SeroKlir ELISA (Kantaro-EKF Diagnostics). Patients with a corrected antibody level of <0.7 AU/mL were considered seronegative. Results: Four hundred ninety-five AZ and 141 Pfizer patients had a sample analyzed after first dose and 593 after second dose (346 AZ versus 247 Pfizer). After first dose, 25.7% of patients seroconverted (26.6% AZ, 22.8% Pfizer). After second dose, 148 (42.8%) of AZ seroconverted compared with 130 (52.6%) of Pfizer ( P  = 0.02; hazard ratio, 1.48; 95% confidence interval, 1.07-2.06). When negative responders were excluded, Pfizer patients were shown to have significantly higher response than AZ patients (median 2.6 versus 1.78 AU/mL, P  = 0.005). Patients on mycophenolate had a reduced seroconversion rate (42.2% versus 61.4%; P < 0.001; hazard ratio, 2.17) and reduced antibody levels (0.47 versus 1.22 AU/mL, P  = 0.001), and this effect was dose dependent ( P  = 0.05). Prednisolone reduced the seroconversion from 58.2% to 43.6% ( P  = 0.03) among Pfizer but not AZ recipients. Regression analysis showed that antibody levels were reduced by older age ( P  = 0.002), mycophenolate ( P < 0.001), AZ vaccine (versus Pfizer, P  = 0.001), and male gender ( P  = 0.02). Sixteen of 17 serious postvaccine infections occurred to patients who did not seroconvert. Conclusions: Both seroconversion and antibody levels are lower in AZ compared with Pfizer vaccinated recipients following 2 vaccine doses. Mycophenolate was associated with lower antibody responses in a dose-dependent manner. Serious postvaccine infections occurred among seronegative recipients.